Autoimagem de mulheres em tratamento do câncer de mama - OLIVEIRA, Cleidiane Cristina Sousa da Silva de (2025)
Cancer is the leading public health problem worldwide, being the second leading cause of death, second only to cardiovascular diseases. The diagnosis of breast cancer brings not only physiological damages and repercussions but also significant emotional impacts on the affected individuals. The objective of this research was to evaluate the impact of breast cancer treatment on the self-image of women undergoing treatment. It is a cross-sectional study with a quantitative approach, conducted at the Aldenora Bello Cancer Hospital, with 126 women aged 18 or older, undergoing oncological treatment for at least 3 months, from May 2024 to October 2024.Two questionnaires were applied, the first with demographic, socioeconomic, and clinical condition data, and the second with the Body Scale Image Scale. Statistical analysis was performed using IBM SPSS Statistics 22, and changes in body image were assessed using the non-parametric Mann Whitney and Kruskal-Wallis tests. The research results showed that the most common age range was 40 to 49 years, 58% had a partner, 79.4% were mixed-race, 53.2% had completed high school, 81% had a family income of 1 to 2 minimum wages, 78.6% of participants had been in treatment for 3 months to 1 year, 58.7% did not have comorbidities, and the most prevalent health issues were systemic hypertension (20.6%) and diabetes mellitus. Among the women, 51.6% considered their body image slightly altered, 27.8% moderately altered, and 12.7% significantly altered. It was also found that age, mental health monitoring, and partial mastectomy surgery were significantly associated with changes in body image. It is crucial for healthcare professionals, particularly nurses, to recognize the importance of body image in the context of breast cancer treatment and adopt holistic, patient-centered approaches to provide adequate support to women throughout this process.